Communal Rights as the Hegemony in Third World Regime: An Indonesian Perspective - Putri, Yunita Maya; Putri, Ria Wierma; Tisnanta, HS (UI Scholars Hub, 2022)
The birth of international law was a direct result of the emergence of civilized and independent states in the sixteenth century in Europe, known as the Enlightenment. So the need for a series of rules to regulate legal relations between these countries. However, until now, Asian and African countries are still fighting for their independence until new problems arise. The polarization of the international community is divided into two, namely developed and developing countries. Where international law is dominated by developed countries with European and American values and does not accommodate the values of local wisdom from developing countries that were former colonies. Indonesia as a developing country must be able to take appropriate steps to anticipate all changes and developments as well as global trends so that national goals can be achieved. One of the important steps taken is to promote and protect their communal rights. The concept of recognizing communal rights originating from developed countries and being accommodated in various international agreements such as The General Agreement on Tariffs and Trade (GATT) and Trade Related Aspects of Intellectual Property Rights (TRIPs) which are more in favor of the economic interests and investment of countries progress without paying attention to the disparity in the ability to master knowledge, technology, and information as intangible capital, especially communal rights. The monopoly of intangible capital by developed countries is not in favor of developing countries as owners of communal wealth that should receive appreciation and recognition, as well as economic benefits for developing countries. Indonesia as a developing country rich in natural resources, arts, and culture has various communal assets that require legal recognition and protection and are recognized internationally. Communal rights that are currently developing in Indonesia are a response to the hegemony of communal wealth controlled by developed countries to maintain national identity. The dynamics of the global economy that is driven by knowledge, creativity and technology must not ignore communal rights as part of the domestic economic system. Instead of being skeptical about this, Indonesia as a developing country must determine a strategy to utilize communal rights as intangible capital in economic development. By using a literature study, this paper describes the advantages and challenges in protecting communal rights and their benefits in Indonesia. Communal intellectual property is a form of recognition for the traditional culture of the Indonesian people to be preserved and generate economic benefits for the entire custodial community. In addition, communal intellectual property is protected by the state with unlimited protection which will provide welfare for indigenous peoples. However, there are still some shortcomings in the protection of communal intellectual property because there is still no written and systematic inventory of the traditional cultures produced by indigenous peoples, as well as the registration model and benefit sharing by the state to the custodian community. Government policies are needed to gradually provide effective and efficient protection in the form of defensive protection and the sui generis law.